The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.neuroscience.2014.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin reverses the downregulation of M1/4 receptor binding in 6-hydroxydopamine-induced parkinsonian rats: The association with improvements in long-term memory

Abstract: . (2014). Simvastatin reverses the downregulation of M1/4 receptor binding in 6-hydroxydopamine-induced parkinsonian rats: the association with improvements in long-term memory. Neuroscience, 267 57-66.Simvastatin reverses the downregulation of M1/4 receptor binding in 6-hydroxydopamine-induced parkinsonian rats: the association with improvements in long-term memory AbstractBackground It is believed that muscarinic M1/4 receptors are closely correlated to the dopaminergic system and are strongly involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…These results combined with another study that was published by our group on the same rats and treatments in this study found longterm memory impairments were prevented in 6-OHDA rats treated with simvastatin [56]. By testing the rats in a Morris Water Maze, it was observed that 6-OHDA rats treated with simvastatin (10 mg/kg/day) had a significantly shorter total distance travelled that resembled the control rats.…”
Section: Simvastatin Attenuated the Declined Cb1 Receptor Expressionssupporting
confidence: 84%
“…These results combined with another study that was published by our group on the same rats and treatments in this study found longterm memory impairments were prevented in 6-OHDA rats treated with simvastatin [56]. By testing the rats in a Morris Water Maze, it was observed that 6-OHDA rats treated with simvastatin (10 mg/kg/day) had a significantly shorter total distance travelled that resembled the control rats.…”
Section: Simvastatin Attenuated the Declined Cb1 Receptor Expressionssupporting
confidence: 84%
“…They argued that chronic inflammation offers a clear biochemical mechanism which can promote the development of PD. Huang et al [ 44 ] recently showed in multiple models that Simvastatin ameliorated memory deficits in patients with Alzheimer’s disease as well as in laboratory models of AD, and that it achieved this through reduction of mRNA expression of inflammatory cytokines and mediators as well as by improving neuronal survival, supporting earlier work by Wang et al [ 45 ].…”
Section: Why Does Simvastatin Represent a Strong Candidate To Be A DImentioning
confidence: 53%
“…Quantification of binding sites was performed using a high‐resolution Beta Imager (BioSpace, Paris, France) according to our previous studies . Briefly, sections were placed in a sample holder inside the detection chamber of the Beta Imager.…”
Section: Methodsmentioning
confidence: 99%